2020
DOI: 10.3390/cells9122616
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ARHGAP29 on the Invasion of Mesenchymal-Transformed Breast Cancer Cells

Abstract: Aggressive and mesenchymal-transformed breast cancer cells show high expression levels of Rho GTPase activating protein 29 (ARHGAP29), a negative regulator of RhoA. ARHGAP29 was the only one of 32 GTPase-activating enzymes whose expression significantly increased after the induction of mesenchymal transformation in breast cancer cells. Therefore, we investigated the influence of ARHGAP29 on the invasiveness of aggressive and mesenchymal-transformed breast cancer cells. After knock-down of ARHGAP29 using siRNA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 60 publications
0
7
0
9
Order By: Relevance
“…The tumor suppresser, 12- O -Tetradecanoyl phorbol-13-acetate (TPA)-inducible sequences 21 (TIS21), an ortholog of B-cell translocation gene 2 (BTG2), inhibited TNBC cell growth and invasion via activation of Akt1 and not Akt2 [ 169 ]. A recent study showed that Rho GTPase activating protein 29 (ARHGAP29) interacted with Akt1 and knockdown of ARHGAP29 decreased invasion of breast cancer cells [ 170 ]. While ARHGAP29 knockdown downregulated Akt1, the ratio of phosphorylated Akt1 to total Akt1 remained unchanged.…”
Section: Function Of Akt Isoformsmentioning
confidence: 99%
“…The tumor suppresser, 12- O -Tetradecanoyl phorbol-13-acetate (TPA)-inducible sequences 21 (TIS21), an ortholog of B-cell translocation gene 2 (BTG2), inhibited TNBC cell growth and invasion via activation of Akt1 and not Akt2 [ 169 ]. A recent study showed that Rho GTPase activating protein 29 (ARHGAP29) interacted with Akt1 and knockdown of ARHGAP29 decreased invasion of breast cancer cells [ 170 ]. While ARHGAP29 knockdown downregulated Akt1, the ratio of phosphorylated Akt1 to total Akt1 remained unchanged.…”
Section: Function Of Akt Isoformsmentioning
confidence: 99%
“…Abbildung 2: Schematische Darstellung der Schnittmenge von 223 durch induzierte EMT hochregulierten Genen und 32 in Microarrays betrachteten Rho GTPase aktivierenden Proteinen(Kolb et al 2020). Bestehende Microarray-Daten(Ziegler 2013; Ziegler et al 2014) zum Vergleich der Genexpression von MCF-7-Wildtyp-Zellen und generierten mesenchymal transformierten MCF-7-EMT-Zellen wurden hinsichtlich der Hochregulierung der Expression ausgewählter Gene erneut analysiert(Kolb et al 2020). Unter den betrachteten Genen befanden sich 32 bis dato als Rho GTPase aktivierende Proteine anerkannte Gene(Kolb et al 2020).…”
unclassified
“…Bestehende Microarray-Daten(Ziegler 2013; Ziegler et al 2014) zum Vergleich der Genexpression von MCF-7-Wildtyp-Zellen und generierten mesenchymal transformierten MCF-7-EMT-Zellen wurden hinsichtlich der Hochregulierung der Expression ausgewählter Gene erneut analysiert(Kolb et al 2020). Unter den betrachteten Genen befanden sich 32 bis dato als Rho GTPase aktivierende Proteine anerkannte Gene(Kolb et al 2020). Es zeigte sich bei 223 Genen eine Hochregulation durch die induzierte EMT in den MCF-7-EMT-Zellen im Vergleich zu den MCF-7-Wildtyp-Zellen (Ziegler 2013).…”
unclassified
See 2 more Smart Citations